A Community-Wide Walking Promotion Using Maps and Events for Japanese Older Adults. (18th May 2019) - Kubota, Akio; Matsushita, Munehiro; Arao, Takashi; Merom, Dafna; Cerin, Ester; Sugiyama, Takemi
Objective: This study evaluated the effect of a community-wide walking intervention (involving walking maps and events) on older residents' walking and environmental perceptions.Method: In this nonrandomized quasi-panel study, older adults living in an intervention and control site were recruited at baseline and follow-up. All households in the intervention site received maps and were invited to participate in a walking event monthly. The intervention lasted for 21 months. The outcomes were walking frequency, duration, and perceptions of local environments.Results: We did not find a significant improvement in walking frequency or duration in the intervention site relative to the control site. However, there was a significant increase in the awareness of others being active and a marginal increase in the perception of aesthetics in the intervention site.Discussion: The increased awareness of others being active may be a positive step in the stages of change toward engagement in physical activity.